ANALYSIS OF FOREIGN POLICY OF THE REPUBLIC OF KAZAKHSTAN IN FOREIGN ELECTRONIC MEDIA: APPLICATION EXPERIMENT OF MATHEMATICAL-STATISTICAL METHODS AND COMPUTER TECHNOLOGIES - Zhakisheva, S.; Slavko, T.; Utesheva, E. (Journal of history, 2018)
The formulation of the problem of studying the foreign policy activity of the Republic of Kazakhstan on the basis of the materials of the leading English and Russian language press using content analysis, mathematical and statistical research methods and computer data processing technologies is extremely important for our country, as it actualizes the question of how Kazakhstan’s reputation in the international arena coincides with the image created by PR-management of the country. An attempt to give a more objective answer, based on scientifically based research methods and data from reputable global media, is being undertaken in this paper.